Síntese paralela e estudos de relação estrutura-atividade e de toxicidade seletiva de nitroderivados ativos contra Leishmania sp - Andre, Fernanda Rosa [UNIFESP] (2015)
Leishmaniasis is a group of diseases considered neglected according to the World Health Organization, which affects about 350 million people worldwide. They are caused by protozoa of the genus Leishmania, transmitted in their promastigote form by the bite of the female sandfly vector insect. Chemotherapy of leishmaniasis is rather scarce and limited presenting significant toxic side effects, and high propensity to emergence of resistance. Leishmania cysteine ??proteases seem to be correlated with invasiveness parasite to the host cells as well as their nourishment inside the same and, finally, the exhaust mechanisms of the immune system parasites. Inhibitors of these proteases are shown as potential agents for the treatment of leishmaniasis. Nitroderivatives have their antiprotozoal activity recently linked to the inhibition of cysteine ??proteases, as well as its additional mechanism of free radical production by reducing the nitro group by nitroreductase. This study aimed to search for new compounds leishmanicidal by application of parallel synthesis for compound analogs of N-nitro-derivatives acilidrazônicos, aimed at understanding the structural characteristics which result in such activity in vitro, coupled with the desired low toxicity chemotherapy. The final synthesized compounds were subjected to biological tests against Leishmania amazonensis five different concentrations (25 ug / mL to 0.78 ug / ml). The compounds 4-methoxy and 4-methyl-2 - [(5-nitro-2-thiophenyl) methylene] hydrazide showed the better biological activity, with 2.51 and 2.77 uM, respectively, IC50. The substitution of thiophene for its isostere benzene leads to decreased leishmanicidal activity, thus indicating the importance of the sulfur heteroatom to this activity. Moreover, compounds lacking the nitro group in their structures showed antileishmanial activity, although at higher concentrations compared to their nitrated analogues. These results indicate that the nitro group appears to be important for activity, but not essential. Qualitative studies of the relationship between chemical structure and biological activity were carried out and at the end of the analysis, it was possible to understand that the synthesized series should act not only in nitroredutases when present reduction of subject group, but also cysteine ??proteases or other still unknown targets.